Human IgG antibody responses to severe acute respiratory syndrome coronavirus 2 viral antigens receptor-binding domain, spike, and nucleocapsid, in vaccinated adults from Merida, Mexico - Puerta-Guardo, Henry; Parra-Cardeña, Manuel; Peña-Miranda, Fernando; Flores-Quintal, Felipe; Granja-Pérez, Pilar; Villanueva-Jorge, Salha; González-Losa, Refugio; Conde-Ferraez, Laura; Gómez-Carballo, Jesus; Vazquez-Prokopec, Gonzalo; Earnest, James T.; Manrique-Saide, Pablo; et al. (Frontiers in Medicine, 2022)
Several vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been approved for controlling the coronavirus disease 2019 (COVID-19) pandemic worldwide. Antibody response is essential to understand the immune response to different viral targets after vaccination with different vaccine platforms. Thus, the main aim of this study was to describe how vaccination with two distinct SARS-CoV-2 vaccine preparations elicit IgG antibody specific responses against two antigenically relevant SARS-CoV-2 viral proteins: the receptor-binding domain (RBD) and the full-length spike (S). To do so, SARS-CoV-2 protein specific in-house enzyme-linked immunosorbent assays (ELISAs) were standardized and tested against serum samples collected from 89 adults, recipients of either a single-dose of the Spike-encoding mRNA-based Pfizer/BioNTech (Pf-BNT) (70%, 62/89) or the Spike-encoding-Adenovirus-5-based CanSino Biologics Inc. (CSBIO) (30%, 27/89) in Merida, Mexico. Overall, we identified an IgG seroconversion rate of 88% (68/78) in all vaccinees after more than 25 days post-vaccination (dpv). Anti-RBD IgG-specific responses ranged from 90% (46/51) in the Pf-BNT vaccine at 25 dpv to 74% (20/27) in the CSBIO vaccine at 42 dpv. Compared to the S, the RBD IgG reactivity was significantly higher in both Pf-BNT (p < 0.004) and CSBIO (p < 0.003) vaccinees. Interestingly, in more than 50% of vaccine recipients, with no history of COVID-19 infection, antibodies against the nucleocapsid (N) protein were detected. Thus, participants were grouped either as naïve or pre-exposed vaccinees. Seroconversion rates after 25 and more dpv varies between 100% in Pf-BNT (22/22) and 75% (9/12) in CSBIO pre-exposed vaccinees, and 89% (26/29) and 73% (11/15) in Pf-BNT and CSBIO naïve vaccine recipients, respectively. In summary, observed seroconversion rates varied depending on the type of vaccine, previous infection with SARS-CoV-2, and the target viral antigen. Our results indicate that both vaccine preparations can induce detectable levels of IgG against the RBD or Spike in both naïve and SARS-CoV-2 pre-exposed vaccinees. Our study provides valuable and novel information about the serodiagnosis and the antibody response to vaccines in Mexico.